The value of involving patients and public in health services research and evaluation: a qualitative study - Saini, Pooja (Res Involv Engagem, 2021)
BACKGROUND: Public and Patient Involvement, Engagement and Participation research encompasses working with patients/service users (people with a medical condition receiving health service treatment), public members, caregivers and communities (who use services or care for patients). The Partner Priority Programme (PPP) was developed by the National Health Service [NHS] and National Institute for Health Research Collaboration for Leadership in Applied Health Research and Care [NIHR CLAHRC] NWC to share information and experience on evaluating new services being offered to patients that were seeking to reduce health inequalities, improve people’s health and wellbeing and reduce emergency hospital admissions. This paper seeks to explore an approach developed for involving the public as equal partners within the evaluation and decision-making processes of health and social care services research. The aim of this study was to identify how public advisors were included, the impact of their involvement, and how change occurred within the organisations following their involvement. METHODS: A qualitative approach using focus group discussions was adopted to explore the experiences of two cohorts of participants involved in PPP project teams. Focus groups were held with public advisors (n = 9), interns (n = 9; staff or public who received a funded internship for a PPP project), NHS and Local Authority initiative leads (n = 10), and academic facilitators (n = 14). These were transcribed verbatim and analysed using a thematic approach. RESULTS: Thirty-two public advisors were recruited to support 25 PPP projects across the Collaboration for Leadership in Applied Health Research and CLAHRC North West Coast [NWC] partner organisations. Three inter-related themes were conceptualised: 1)“Where it all started - involving public advisors” identified the varying journeys to recruitment and experiences of becoming a public advisor; 2)“Steps toward active involvement and engagement” related to public advisors becoming core team members; and 3) “Collaborative working to enhance public and patient involvement” relayed how projects identified the benefits of working jointly with the public advisors, particularly for those who had not experienced this style of working before. CONCLUSIONS: The findings indicate that the PPP model is effective for embedding Public and Patient Involvement [PPI] within health services research, and recommends that PPI is integrated at the earliest opportunity within research projects and service evaluations through the use of support-led and facilitative programmes.